Tracking Potentiating States of Dissociation: An Intensive Clinical Case Study of Sleep, Daydreaming, Mood, and Depersonalization/Derealization - Poerio, Giulia L.; Kellett, Stephen; Totterdell, Peter (Frontiers in Psychology, 2016)
This study examined in real time the role of sleep and daydreaming as potentiating states for subsequent dissociation in depersonalization/derealization disorder (DDD). Research and theory suggests that dissociation may be exacerbated and maintained by a labile sleep-wake cycle in which “dream-like” mentation intrudes into waking life and fuels dissociative symptoms. We explore and extend this idea by examining the state of daydreaming in dissociation. Daydreaming is a state of consciousness between dreaming and waking cognition that involves stimulus-independent and task-unrelated mentation. We report the results of a unique intensive N = 1 study with an individual meeting diagnostic criteria for DDD. Using experience-sampling methodology, the participant rated (six times daily for 40 days) current daydreaming, mood, and dissociative symptoms. At the start of each day sleep quality and duration was also rated. Daydreaming was reported on 45% of occasions and significantly predicted greater dissociation, in particular when daydreams were repetitive and negative (but not fanciful) in content. These relationships were mediated by feelings of depression and anxiety. Sleep quality but not duration was a negative predictor of daily dissociation and also negatively predicted depression but not anxiety. Findings offer initial evidence that the occurrence and content of daydreams may act as potentiating states for heightened, in the moment, dissociation. The treatment implications of targeting sleep and daydreaming for dissociative disorders are discussed.